Model Pengembangan Kawasan Wisata Pedesaan Melalui Pendekatan Partisipasi Masyarakat (Studi Kasus Desa Tegalwaru, Ciampea, Bogor) - Subagyo, Wawan Hari; Andayani, Asti (Jurnal Ilmiah Pariwisata, 2019)
Kampoeng Wisata Bisnis Tegalwaru (Tegalwaru Business Tourism Campoeng) is a rural tourism area model that empowers micro, small and medium enterprises (MSMEs) as the main tourist attraction. This tourist area synergizes between tourism and MSME business activities in the Tegalwaru village so as to increase the prosperity of the Tegalwaru village community. This study analyzes the condition of tourist areas, rating tourists, community participation and tourism development efforts. Tourists consider that there needs to be a souvenir kiosk in the village of Tegalwaru. Kampoeng Tegalwaru business tourism is a model of rural tourism that involves community participation starting from the planning, implementation and evaluation stages of the program so as to increase community income. The concept of community participation in the rural tourism area of Kampoeng Tegalwaru Business Tourism was initiated, guided, fostered and directed by change agents, namely Mrs. Tatiek Kancaniati. The results of the Analitycal Hierarchy Process (AHP) show that the most important effort to develop the Kampoeng Wisata Bisnis Tegalwaru is to expand product marketing.